The Developing of Minangkabau Customary Inheritance - Judiasih, Sonny Dewi; Kusmayanti, Hazar; Rajamanicham, Ramalinggam; Artiana, Maureen Maysa (Media Iuris, 2025)
The matrilineal kinship system draws a female line. The problem of inheritance law becomes more complex if it occurs within the Minangkabau Indigenous Community. This is motivated by the fact that the Minangkabau Indigenous People are devout followers of Islam; they also have strong customary laws with matrilineal lineage and collective inheritance systems. The author uses a juridical-normative research method, while the research specification is descriptive and analytical. The data obtained was analyzed using qualitative juridical methods. In several inheritance disputes, judges of the Religious Courts in West Sumatra have applied the principle of “Adat Basandi Syarak, Syarak Basandi Kitabullah.” In implementing the inheritance system, Minangkabau customary law aligns with Islamic law without eliminating the values of the adat. The existing customary law must be subordinate to Sharia, that is, Islamic law derived from the Qur’an and Sunnah as the Kitabullah. Every customary rule must not deviate from Islamic Sharia, including inheritance law. In addition to following customary provisions, inheritance must also be in accordance with Islamic inheritance law, in this case, Faraidh.